2016
DOI: 10.1038/nature17435
|View full text |Cite
|
Sign up to set email alerts
|

Restoring cortical control of functional movement in a human with quadriplegia

Abstract: Millions of people worldwide suffer from diseases that lead to paralysis through disruption of signal pathways between the brain and the muscles. Neuroprosthetic devices are designed to restore lost function and could be used to form an electronic 'neural bypass' to circumvent disconnected pathways in the nervous system. It has previously been shown that intracortically recorded signals can be decoded to extract information related to motion, allowing non-human primates and paralysed humans to control computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
648
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 776 publications
(686 citation statements)
references
References 29 publications
4
648
0
1
Order By: Relevance
“…Recently, human BMIs have shown that learned control of multiple neurons can operate different types of external devices to facilitate communication and motor control in people with paralysis. For example, on the basis of activity in the primary motor cortex (M1) recorded from intracortical multielectrode arrays, individuals with partial paralysis were able to learn coordinated movements of a seven degrees-of-freedom robotic arm 13 , to control a computer cursor 14 or to functionally stimulate muscles 15 .…”
Section: Coherencementioning
confidence: 99%
“…Recently, human BMIs have shown that learned control of multiple neurons can operate different types of external devices to facilitate communication and motor control in people with paralysis. For example, on the basis of activity in the primary motor cortex (M1) recorded from intracortical multielectrode arrays, individuals with partial paralysis were able to learn coordinated movements of a seven degrees-of-freedom robotic arm 13 , to control a computer cursor 14 or to functionally stimulate muscles 15 .…”
Section: Coherencementioning
confidence: 99%
“…The neuromuscular system can be interfaced at various levels to extract neural signals that code the intended movement, e.g., via brain, nerve or muscle recordings [4][5][6][7][8][9] . Although direct brain signal decoding provides the neural information associated to movement intention and control [10][11][12] , peripheral approaches (nerves or muscles) are so far the only clinically viable solutions for re-establishing upper limb function in amputees 4,13 . In these patients, the availability of nerve and muscle structures above the amputation allows access to neural information at the output of the spinal cord circuitries.…”
mentioning
confidence: 99%
“…Application of the motor subtest of the GRASSP tool was confirmed in four studies. 9,24,51,58 It evaluates the upper limbs through MMT on a scale of six points. 26 The modified Brunstron and Dennem grading scale was applied in three studies.…”
Section: Resultsmentioning
confidence: 99%